2021
DOI: 10.3389/fcomp.2021.624558
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Alzheimer’s Dementia From the Transcriptions of Spontaneous Speech Using fastText and CNN Models

Abstract: Alzheimer’s dementia (AD) is a type of neurodegenerative disease that is associated with a decline in memory. However, speech and language impairments are also common in Alzheimer’s dementia patients. This work is an extension of our previous work, where we had used spontaneous speech for Alzheimer’s dementia recognition employing log-Mel spectrogram and Mel-frequency cepstral coefficients (MFCC) as inputs to deep neural networks (DNN). In this work, we explore the transcriptions of spontaneous speech for deme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…More specifically, BERT outperforms all the research works, except [15], in terms of Accuracy by 2.08-8.33%, in F1-score by 1.33-8.68%, and in Recall by 2.66-14.99%. Moreover, BERT+Co-Attention surpasses [22], [27], [28] in Accuracy by 2.50%, 0.42%, and 4.58% respectively. Also, it surpasses [22], [27], [28] in Recall by 17.49%, 5.16%, and 9.16% respectively.…”
Section: A Single-task Learning Experimentsmentioning
confidence: 92%
See 3 more Smart Citations
“…More specifically, BERT outperforms all the research works, except [15], in terms of Accuracy by 2.08-8.33%, in F1-score by 1.33-8.68%, and in Recall by 2.66-14.99%. Moreover, BERT+Co-Attention surpasses [22], [27], [28] in Accuracy by 2.50%, 0.42%, and 4.58% respectively. Also, it surpasses [22], [27], [28] in Recall by 17.49%, 5.16%, and 9.16% respectively.…”
Section: A Single-task Learning Experimentsmentioning
confidence: 92%
“…We extend this research work by employing more transformer-based networks with an efficient training strategy, proposing a new interpretable method to detect AD patients based on siamese networks, introducing two models in a multi-task learning framework by regarding the MMSE prediction task as a multiclass classification task and employing explainability techniques. On the other hand, research works [27] & [28] introduced deep learning models including CNNs and LSTM neural networks with feed-forward highway layers respectively. In [27] results suggested that the utterances of the interviewer boost the classification performance.…”
Section: B Deep Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Meghanani et al ( 2021b ) introduced some approaches to detect AD patients and predict the MMSE scores using only text data. Specifically, the authors proposed a Convolutional Neural Network (CNN) and fastText-based classifiers.…”
Section: Related Workmentioning
confidence: 99%